Flexible nanofilms coated with aligned piezoelectric microfibers preserve the contractility of cardiomyocytes. (September 2017) - Gouveia, P. José; Rosa, S.; Ricotti, L.; Abecasis, B.; Almeida, H.V.; Monteiro, L.; Nunes, J.; Carvalho, F. Sofia; Serra, M.; Luchkin, S.; Kholkin, A. Leonidovitch; Alves, P. Marques; et al.
Abstract: The use of engineered cardiac tissue for high-throughput drug screening/toxicology assessment remains largely unexplored. Here we propose a scaffold that mimics aspects of cardiac extracellular matrix while preserving the contractility of cardiomyocytes. The scaffold is based on a poly(caprolactone) (PCL) nanofilm with magnetic properties (MNF, standing for magnetic nanofilm) coated with a layer of piezoelectric (PIEZO) microfibers of poly(vinylidene fluoride–trifluoroethylene) (MNF+PIEZO). The nanofilm creates a flexible support for cell contraction and the aligned PIEZO microfibers deposited on top of the nanofilm creates conditions for cell alignment and electrical stimulation of the seeded cells. Our results indicate that MNF+PIEZO scaffold promotes rat and human cardiac cell attachment and alignment, maintains the ratio of cell populations overtime, promotes cell-cell communication and metabolic maturation, and preserves cardiomyocyte (CM) contractility for at least 12 days. The engineered cardiac construct showed high toxicity against doxorubicin, a cardiotoxic molecule, and responded to compounds that modulate CM contraction such as epinephrine, propranolol and heptanol.